CRC and NHPWM method for test bench based on cascaded converter. Issue 1 (1st January 2019) - Hu, Yaowei; Yang, Ranchen; Shao, Yuting; Chen, Guozhu
Abstract : This study describes a megawatt test bench based on the cascaded converter for the stability test of renewable energy generation system under different grid disturbances. The test bench is composed of two cascaded converters, which are used to control the output of fundamental voltage and harmonic voltage. Aiming at the defects of the traditional repetitive controller (RC) and hybrid pulse‐width modulation (HPWM) method, configurable RC (CRC) and novel HPWM (NHPWM) method are presented. By flexibly configuring the zeros and poles of CRC, the harmonic order that can be tracked accurately and the time delay of CRC can be easily changed. Besides, with NHPWM, the number of modules modulated by carrier phase‐shifted PWM can be arbitrarily configured according to the output voltage quality and switching loss. Therefore, the flexible CRC and NHPWM are beneficial to achieve high control accuracy of fundamental and harmonic voltage and fast dynamic response while considering the switching loss, which is verified by simulation. The detailed harmonic analysis and calculation method of NHPWM are given, which are also proved correct by comparison of theoretical calculation and simulation results.